High-strength polypropylene urine cup and preparation process thereof

Through the preparation of modified polypropylene materials, combined with modified talc powder and other modifiers, the problem of insufficient strength and transparency of polypropylene is solved, and the polypropylene materials with high strength, high transparency and antistatic properties are achieved, and its application in the medical field has been expanded.

CN119798857AInactive Publication Date: 2025-04-11JIANGSU XINKANG MEDICAL EQUIP CO LTD

Patent Information

Application Number
CN202510107197.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-04-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The insufficient strength and transparency of polypropylene limits its application in the field of medical devices.

Method used

Using high-strength polypropylene material, polypropylene with high strength, high transparency and antistatic properties are prepared through the synergy of modified polypropylene, modified talc, maleic anhydride grafted polypropylene, high-density polyethylene and toughener.

Benefits of technology

The strength and transparency of polypropylene are significantly improved, making it more suitable for use in the medical device field, and extending the application range of polypropylene products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005255769380000101
    Figure BDA0005255769380000101
Patent Text Reader

Abstract

The invention discloses a high-strength polypropylene urine cup and a preparation process thereof, and relates to the technical field of polypropylene. The high-strength polypropylene urine cup is prepared from a high-strength polypropylene material through plasticizing, injection molding and compression molding. The high-strength polypropylene material is prepared from the following raw material components in parts by weight: 100 parts of homo-polypropylene, 10 to 20 parts of modified polypropylene, 10 to 15 parts of maleic anhydride grafted polypropylene, 5 to 12 parts of modified talcum powder, 5 to 10 parts of high-density polyethylene, 0.1 to 0.2 part of beta-nucleating agent, 2 to 4 parts of flexibilizer, 1.5 to 3 parts of lubricant, 0.5 to 1 part of antioxidant and 1 to 2 parts of antistatic agent. Through the synergistic effect of the modified polypropylene, maleic anhydride grafted polypropylene, high-density polyethylene, modified talcum powder and other raw materials, the high-strength polypropylene material with high strength and high transparency is comprehensively obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polypropylene, in particular to a high-strength polypropylene urine cup and a preparation process thereof. Background Art

[0002] Polypropylene (PP) is a semi-crystalline polymer, originally synthesized by Guilio Natta by polymerizing propylene monomers using a Ziegler-Natta catalyst. Depending on the different positions of the methyl groups in the PP molecular chain, there are three basic types of PP: isotactic PP, syndiotactic PP, and atactic PP. PP has the characteristics of light weight, stable chemical properties, excellent weather resistance, good barrier properties, and easy processing and molding. It is widely used in various fields of national economy and people's livelihood, such as vehicles, aerospace, ocean, packaging, and home furnishings, providing great convenience for people's lives. It has now become the second largest polyolefin product after polyethylene (PE).

[0003] However, on the one hand, PP has relatively poor low temperature resistance and impact resistance; on the other hand, PP is a partially crystalline resin. Under normal processing conditions, the crystallization speed is relatively slow, and it is easy to form large spherulites, which makes it difficult for light to pass through the entire PP product. Therefore, the transparency and glossiness of PP products are poor, and the appearance lacks aesthetic appeal, which limits its application in the field of medical devices. In order to improve the transparency of PP, a small amount of nucleating agent is generally added to PP to obtain PP with higher transparency. However, the strength of PP obtained by this method cannot be greatly improved, which also limits its application to a certain extent. Adding fillers can improve the mechanical strength of PP, but it has a great impact on the transparency of the product, and the haze value is significantly improved, which does not have practical application value.

[0004] In summary, in order to solve the above problems, the present invention proposes a high-strength polypropylene urine cup and a preparation process thereof, which solves the defects of low strength and low transparency of PP, enabling it to be applied to the field of medical devices, which is of great significance. Summary of the invention

[0005] The object of the present invention is to provide a high-strength polypropylene urine cup and a preparation process thereof to solve the problems raised in the above-mentioned background technology.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0007] A high-strength polypropylene urine cup is prepared from a high-strength polypropylene material; the high-strength polypropylene material comprises the following raw materials: by weight, 100 parts of homopolymer polypropylene, 10-20 parts of modified polypropylene, 10-15 parts of maleic anhydride grafted polypropylene, 5-12 parts of modified talc, 5-10 parts of high-density polyethylene, 0.05-0.2 parts of a β-nucleating agent, 2-4 parts of a toughening agent, 1.5-3 parts of a lubricant, 0.5-1 parts of an antioxidant, and 1-2 parts of an antistatic agent.

[0008] Furthermore, the method for preparing the high-strength polypropylene material comprises the following steps:

[0009] S1: Preparation of modified polypropylene:

[0010] S11: adding chlorinated polypropylene to toluene, stirring and heating to 50-70° C. to dissolve the polypropylene, thereby obtaining a resin solution;

[0011] S12: heating the resin solution to 90-110° C., adding allyl alcohol polyoxyethylene ether, sodium allyl sulfonate and an initiator thereto, stirring and reacting for 6-12 hours, and purifying to obtain modified polypropylene;

[0012] S2: Preparation of modified talc:

[0013] S21: adding talcum powder and dopamine hydrochloride to deionized water, stirring and mixing, adjusting the pH to 7-8, adding horseradish peroxidase thereto, stirring and mixing, then adding hydrogen peroxide thereto, finally heating to 35-50° C., stirring and reacting for 0.5-1.5 h, filtering, washing, and drying to obtain polydopamine-coated talcum powder;

[0014] S22: adding polydopamine-coated talc and a silane coupling agent to an ethanol solution, stirring and heating to 50-60° C. for reaction for 1-5 hours, filtering, washing, and drying to obtain silane-modified talc;

[0015] S23: adding silane-modified talc, 3-[bis-(2-hydroxyethyl)-amino]-benzoic acid and p-toluenesulfonic acid to xylene, stirring and heating to 50-60° C. for reaction for 4-8 hours, filtering, washing and drying to obtain hyperbranched modified talc;

[0016] S24: adding hyperbranched talc and hydroxy-terminated polybutadiene acrylonitrile to petroleum ether, stirring and heating to 30-50° C. for reaction for 24-48 hours, filtering, washing and drying to obtain modified talc;

[0017] S3: Preparation of high-strength polypropylene material:

[0018] S31: placing the raw material components in a mixer according to the formula ratio, stirring and mixing at a speed of 50 to 100 r / min for 10 to 30 minutes to obtain a mixed component;

[0019] S32: adding the mixed components into a twin-screw extruder, melt blending, extruding and granulating, and obtaining a high-strength polypropylene material;

[0020] S4: preparing a high-strength polypropylene urine cup: plasticizing the high-strength polypropylene material, injecting it into a mold, and pressing it into shape to obtain a high-strength polypropylene urine cup.

[0021] Furthermore, the mass ratio of the chlorinated polypropylene, allyl alcohol polyoxyethylene ether, sodium allyl sulfonate and initiator is 1:(0.2-0.4):(0.05-0.1):(0.02-0.04).

[0022] Furthermore, the mass ratio of the talcum powder, dopamine hydrochloride and horseradish peroxidase is 10:(0.5-2):(0.001-0.01).

[0023] Furthermore, the average particle size of the talc is 5 to 30 nm.

[0024] Furthermore, the hydrogen peroxide is a 2-4 v / v% hydrogen peroxide aqueous solution, and the ratio of the added amount to the horseradish peroxidase is 1 mL: (0.02-0.1) g.

[0025] Furthermore, the amount of the silane coupling agent added is 10-20% of the mass of the polydopamine-coated talc.

[0026] Furthermore, the silane coupling agent includes but is not limited to any one of 3-chloromethyltriethoxysilane, 3-chloropropyltriethoxysilane and 3-chloropropyltrimethoxysilane.

[0027] Furthermore, the mass ratio of the silane-modified talc, 3-[bis-(2-hydroxyethyl)-amino]-benzoic acid and p-toluenesulfonic acid is 1:(0.5-0.8):(0.005-0.008).

[0028] Furthermore, the mass ratio of the hyperbranched talc to the hydroxy-terminated polybutadiene acrylonitrile is 1:(0.8-1.2).

[0029] Furthermore, the temperature of the melt blending is 190-230° C., the time of the melt blending is 10-30 min, and the screw speed is 100-200 r / min.

[0030] Furthermore, the plasticizing temperature is 190-230°C.

[0031] Furthermore, the grafting rate of the maleic anhydride grafted polypropylene is 1.2-2%.

[0032] Furthermore, the β-nucleating agent is a threonamide compound.

[0033] Furthermore, the toughening agent includes but is not limited to one or a combination of ethylene propylene diene monomer rubber, ethylene propylene diene monomer rubber, styrene-butadiene-styrene block copolymer, and butadiene rubber.

[0034] Furthermore, the lubricant includes but is not limited to one or a combination of zinc stearate, calcium stearate, and magnesium stearate.

[0035] Furthermore, the antioxidant includes but is not limited to a combination of one or more of hindered phenol antioxidants, thioester antioxidants and phosphite antioxidants.

[0036] Furthermore, the antistatic agent is N,N-dihydroxyethyl octadecylamine.

[0037] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0038] (1) In the present invention, allyl alcohol polyoxyethylene ether and sodium allyl sulfonate are grafted onto chlorinated polypropylene; the allyl alcohol polyoxyethylene ether structure can enhance the compatibility and antioxidant properties of polypropylene with other components; the sodium allyl sulfonate structure can improve the antistatic properties of polypropylene;

[0039] (2) Talc can promote the nucleation of polypropylene, which can effectively enhance the strength of polypropylene. In addition, it can also improve the transparency and antistatic properties of polypropylene. However, considering that talc is not well dispersed in polypropylene when directly added, polydopamine is used to coat talc in the present invention, so that its surface has abundant amino groups, and then a hyperbranching reaction occurs with 3-[bis-(2-hydroxyethyl)-amino]-benzoic acid in the subsequent reaction. In addition, a silane coupling agent is used to modify the talc so that its surface has chlorine atoms, so that it can be further grafted with terminal hydroxyl polybutadiene acrylonitrile to obtain modified talc. The modified talc has excellent dispersibility and compatibility, can increase the crosslinking density with polypropylene, and has a significant effect on improving the strength of polypropylene.

[0040] (3) The compatibility of high-density polyethylene and toughening agents in polypropylene is poor. The compatibility can be improved by partially grafting polypropylene with maleic anhydride. By controlling the dosage of the two, high-density polyethylene and toughening agents form an "island structure" in polypropylene, thereby enhancing the toughness and strength of polypropylene.

[0041] In summary, the present invention prepares a polypropylene material with high strength, high transparency and good antistatic properties through the synergistic effect of modified polypropylene, modified talcum powder, maleic anhydride grafted polypropylene, high-density polyethylene and toughening agent, and processes it to prepare urine cups, which enhances the application expansion of polypropylene products in the medical field and is of great significance. DETAILED DESCRIPTION

[0042] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0043] It should be noted that the following parts are by weight, and the purchase manufacturers of all raw materials involved in the present invention include, without any special restrictions, illustratively: In the following examples,

[0044] Homopolymer polypropylene, item number P816277, with a melt index of 12 g / 10 min at 190°C and a load of 2.16 kg; high-density polyethylene, item number H790495, with a melt index of 12 g / 10 min at 190°C and a load of 2.16 kg, were purchased from Shanghai MacLean Biochemical Technology Co., Ltd.

[0045] Maleic anhydride grafted polypropylene, brand 50E803, grafting rate 1.2%, melt index 470g / 10min at 230°C and 2.16kg load, purchased from Dongguan Taotao Plastic Raw Materials Co., Ltd.;

[0046] Chlorinated polypropylene, product number 68442-33-2; sodium allyl sulfonate, purity 99%; dopamine hydrochloride, purity 99%; horseradish peroxidase, purity 99%, CAS number 9003-99-0; p-toluenesulfonic acid, purity 99%; calcium stearate, purity 99%; antioxidant tris(2,4-di-tert-butylphenyl)phosphite, purity 99%; talc, purity 99%, average particle size 10nm; 3-chloropropyltriethoxysilane, purity 99%, all purchased from Hubei Yongkuo Technology Co., Ltd.;

[0047] Allyl alcohol polyoxyethylene ether, CAS No. 27274-31-3, was purchased from Wuhan Jixinyibang Biotechnology Co., Ltd.;

[0048] Styrene-butadiene-styrene block copolymer, brand 1485, purchased from Hongji Plastics Company, Zhangmutou, Dongguan City;

[0049] 3-[Bis-(2-hydroxyethyl)-amino]-benzoic acid, purity 96%, CAS No. 347343-88-8, purchased from Beijing Bailingwei Technology Co., Ltd.;

[0050] The purity of hydroxy-terminated polybutadiene acrylonitrile was 99%, the product number was HTBN, and it was purchased from Wuhan Rongcan Biotechnology Co., Ltd.;

[0051] β-nucleating agent, model NAB-100, purchased from Zibo Kunyu Chemical Co., Ltd.;

[0052] N,N-dihydroxyethyl octadecylamine with a purity of 99% was purchased from Suzhou Liansheng Chemical Co., Ltd.

[0053] Example 1: Preparation process of a high-strength polypropylene urine cup:

[0054] S1: Preparation of modified polypropylene:

[0055] S11: adding chlorinated polypropylene to toluene, stirring and heating to 65° C. to dissolve the chlorinated polypropylene, thereby obtaining a resin solution;

[0056] S12: heating the resin solution to 100° C., adding allyl alcohol polyoxyethylene ether, sodium allyl sulfonate and benzoyl peroxide thereto, stirring and reacting for 10 hours, and purifying to obtain modified polypropylene;

[0057] Among them, the mass ratio of chlorinated polypropylene, allyl alcohol polyoxyethylene ether, sodium allyl sulfonate and benzoyl peroxide is 1:0.3:0.08:0.03;

[0058] S2: Preparation of modified talc:

[0059] S21: adding talcum powder and dopamine hydrochloride to deionized water, stirring and mixing, adjusting the pH to 7.2, adding horseradish peroxidase thereto, stirring and mixing, then adding 3 v / v% hydrogen peroxide aqueous solution thereto, finally heating to 40° C., stirring and reacting for 1 hour, filtering, washing, and drying to obtain polydopamine-coated talcum powder;

[0060] The mass ratio of talc, dopamine hydrochloride and horseradish peroxidase is 10:1.2:0.004; the ratio of the amount of hydrogen peroxide solution added to the horseradish peroxidase is 1 mL:0.05 g;

[0061] S22: adding polydopamine-coated talc and 3-chloropropyltriethoxysilane to a 70 wt % ethanol aqueous solution, stirring and heating to 55° C. for reaction for 3 h, filtering, washing, and drying to obtain silane-modified talc;

[0062] The amount of 3-chloropropyltriethoxysilane added is 15% of the mass of the polydopamine-coated talc;

[0063] S23: adding silane-modified talc, 3-[bis-(2-hydroxyethyl)-amino]-benzoic acid and p-toluenesulfonic acid to xylene, stirring and heating to 55° C. for 6 h, filtering, washing and drying to obtain hyperbranched modified talc;

[0064] The mass ratio of silane-modified talc, 3-[bis-(2-hydroxyethyl)-amino]-benzoic acid and p-toluenesulfonic acid is 1:0.7:0.007;

[0065] S24: adding hyperbranched talc and hydroxy-terminated polybutadiene acrylonitrile to petroleum ether, stirring and heating to 40° C. for reaction for 36 hours, filtering, washing and drying to obtain modified talc;

[0066] Wherein, the mass ratio of hyperbranched talc powder and hydroxy-terminated polybutadiene acrylonitrile is 1:1;

[0067] S3: Preparation of high-strength polypropylene material:

[0068] S31: placing the raw material components in a mixer according to the formula ratio, stirring and mixing at a speed of 100 r / min for 20 minutes to obtain a mixed component;

[0069] S32: adding the mixed components into a twin-screw extruder, melt-blending at 210° C. for 20 min, and extruding and granulating at a screw speed of 150 r / min to obtain a high-strength polypropylene material;

[0070] The raw material components include: by weight, 100 parts of homopolymer polypropylene, 15 parts of modified polypropylene, 13 parts of maleic anhydride grafted polypropylene, 8 parts of modified talc, 8 parts of high-density polyethylene, 0.1 parts of β-nucleating agent, 2.5 parts of styrene-butadiene-styrene block copolymer, 2 parts of lubricant, 0.85 parts of antioxidant, and 1.35 parts of antistatic agent;

[0071] S4: Preparation of high-strength polypropylene urine cup: After the high-strength polypropylene material is heated to 210° C. for plasticization, it is injected into a mold and pressed into shape to obtain a high-strength polypropylene urine cup.

[0072] Example 2: Preparation process of a high-strength polypropylene urine cup:

[0073] S1: Preparation of modified polypropylene:

[0074] S11: adding chlorinated polypropylene to toluene, stirring and heating to 65° C. to dissolve the chlorinated polypropylene, thereby obtaining a resin solution;

[0075] S12: heating the resin solution to 100° C., adding allyl alcohol polyoxyethylene ether, sodium allyl sulfonate and benzoyl peroxide thereto, stirring and reacting for 10 hours, and purifying to obtain modified polypropylene;

[0076] Among them, the mass ratio of chlorinated polypropylene, allyl alcohol polyoxyethylene ether, sodium allyl sulfonate and benzoyl peroxide is 1:0.2:0.05:0.02;

[0077] S2: Preparation of modified talc:

[0078] S21: adding talcum powder and dopamine hydrochloride to deionized water, stirring and mixing, adjusting the pH to 7.2, adding horseradish peroxidase thereto, stirring and mixing, then adding 2 v / v% hydrogen peroxide aqueous solution thereto, finally heating to 40° C., stirring and reacting for 1 hour, filtering, washing, and drying to obtain polydopamine-coated talcum powder;

[0079] The mass ratio of talcum powder, dopamine hydrochloride and horseradish peroxidase is 10:0.5:0.001; the ratio of the amount of hydrogen peroxide solution added to the horseradish peroxidase is 1 mL:0.02 g;

[0080] S22: adding polydopamine-coated talc and 3-chloropropyltriethoxysilane to a 70 wt % ethanol aqueous solution, stirring and heating to 55° C. for reaction for 3 h, filtering, washing, and drying to obtain silane-modified talc;

[0081] Wherein, the amount of 3-chloropropyltriethoxysilane added is 10% of the mass of polydopamine-coated talc;

[0082] S23: adding silane-modified talc, 3-[bis-(2-hydroxyethyl)-amino]-benzoic acid and p-toluenesulfonic acid to xylene, stirring and heating to 55° C. for 6 h, filtering, washing and drying to obtain hyperbranched modified talc;

[0083] The mass ratio of silane-modified talc, 3-[bis-(2-hydroxyethyl)-amino]-benzoic acid and p-toluenesulfonic acid is 1:0.5:0.005;

[0084] S24: adding hyperbranched talc and hydroxy-terminated polybutadiene acrylonitrile to petroleum ether, stirring and heating to 40° C. for reaction for 36 hours, filtering, washing and drying to obtain modified talc;

[0085] Wherein, the mass ratio of hyperbranched talc powder and hydroxy-terminated polybutadiene acrylonitrile is 1:0.8;

[0086] S3: Preparation of high-strength polypropylene material:

[0087] S31: placing the raw material components in a mixer according to the formula ratio, stirring and mixing at a speed of 100 r / min for 20 minutes to obtain a mixed component;

[0088] S32: adding the mixed components into a twin-screw extruder, melt-blending at 210° C. for 20 min, and extruding and granulating at a screw speed of 150 r / min to obtain a high-strength polypropylene material;

[0089] The raw material components include: by weight, 100 parts of homopolymer polypropylene, 15 parts of modified polypropylene, 13 parts of maleic anhydride grafted polypropylene, 8 parts of modified talc, 8 parts of high-density polyethylene, 0.1 parts of β-nucleating agent, 2.5 parts of styrene-butadiene-styrene block copolymer, 2 parts of lubricant, 0.85 parts of antioxidant, and 1.35 parts of antistatic agent;

[0090] S4: Preparation of high-strength polypropylene urine cup: After the high-strength polypropylene material is heated to 210° C. for plasticization, it is injected into a mold and pressed into shape to obtain a high-strength polypropylene urine cup.

[0091] Example 3: Preparation process of a high-strength polypropylene urine cup:

[0092] S1: Preparation of modified polypropylene:

[0093] S11: adding chlorinated polypropylene to toluene, stirring and heating to 65° C. to dissolve the chlorinated polypropylene, thereby obtaining a resin solution;

[0094] S12: heating the resin solution to 100° C., adding allyl alcohol polyoxyethylene ether, sodium allyl sulfonate and benzoyl peroxide thereto, stirring and reacting for 10 hours, and purifying to obtain modified polypropylene;

[0095] Among them, the mass ratio of chlorinated polypropylene, allyl alcohol polyoxyethylene ether, sodium allyl sulfonate and benzoyl peroxide is 1:0.4:0.1:0.04;

[0096] S2: Preparation of modified talc:

[0097] S21: adding talcum powder and dopamine hydrochloride to deionized water, stirring and mixing, adjusting the pH to 7.2, adding horseradish peroxidase thereto, stirring and mixing, then adding 4 v / v% hydrogen peroxide aqueous solution thereto, finally heating to 40° C., stirring and reacting for 1 hour, filtering, washing, and drying to obtain polydopamine-coated talcum powder;

[0098] The mass ratio of talcum powder, dopamine hydrochloride and horseradish peroxidase is 10:2:0.01; the ratio of the amount of hydrogen peroxide solution added to the horseradish peroxidase is 1 mL:0.1 g;

[0099] S22: adding polydopamine-coated talc and 3-chloropropyltriethoxysilane to a 70 wt % ethanol aqueous solution, stirring and heating to 55° C. for reaction for 3 h, filtering, washing, and drying to obtain silane-modified talc;

[0100] Wherein, the amount of 3-chloropropyltriethoxysilane added is 20% of the mass of polydopamine-coated talc;

[0101] S23: adding silane-modified talc, 3-[bis-(2-hydroxyethyl)-amino]-benzoic acid and p-toluenesulfonic acid to xylene, stirring and heating to 55° C. for 6 h, filtering, washing and drying to obtain hyperbranched modified talc;

[0102] The mass ratio of silane-modified talc, 3-[bis-(2-hydroxyethyl)-amino]-benzoic acid and p-toluenesulfonic acid is 1:0.8:0.008;

[0103] S24: adding hyperbranched talc and hydroxy-terminated polybutadiene acrylonitrile to petroleum ether, stirring and heating to 40° C. for reaction for 36 hours, filtering, washing and drying to obtain modified talc;

[0104] Wherein, the mass ratio of hyperbranched talc powder and hydroxy-terminated polybutadiene acrylonitrile is 1:1.2;

[0105] S3: Preparation of high-strength polypropylene material:

[0106] S31: placing the raw material components in a mixer according to the formula ratio, stirring and mixing at a speed of 100 r / min for 20 minutes to obtain a mixed component;

[0107] S32: adding the mixed components into a twin-screw extruder, melt-blending at 210° C. for 20 min, and extruding and granulating at a screw speed of 150 r / min to obtain a high-strength polypropylene material;

[0108] The raw material components include: by weight, 100 parts of homopolymer polypropylene, 15 parts of modified polypropylene, 13 parts of maleic anhydride grafted polypropylene, 8 parts of modified talc, 8 parts of high-density polyethylene, 0.1 parts of β-nucleating agent, 2.5 parts of styrene-butadiene-styrene block copolymer, 2 parts of lubricant, 0.85 parts of antioxidant, and 1.35 parts of antistatic agent;

[0109] S4: Preparation of high-strength polypropylene urine cup: After the high-strength polypropylene material is heated to 210° C. for plasticization, it is injected into a mold and pressed into shape to obtain a high-strength polypropylene urine cup.

[0110] Example 4: Example 4 is based on Example 1, with the following adjustments: In S3, the raw material components include: in parts by weight, 100 parts of homopolymer polypropylene, 10 parts of modified polypropylene, 10 parts of maleic anhydride grafted polypropylene, 5 parts of modified talc, 5 parts of high-density polyethylene, 0.1 parts of β-nucleating agent, 2.5 parts of styrene-butadiene-styrene block copolymer, 2 parts of lubricant, 0.85 parts of antioxidant, and 1.35 parts of antistatic agent.

[0111] Example 5: Example 5 is based on Example 1, with the following adjustments: In S3, the raw material components include: in parts by weight, 100 parts of homopolymer polypropylene, 20 parts of modified polypropylene, 15 parts of maleic anhydride grafted polypropylene, 12 parts of modified talc, 10 parts of high-density polyethylene, 0.1 parts of β-nucleating agent, 2.5 parts of styrene-butadiene-styrene block copolymer, 2 parts of lubricant, 0.85 parts of antioxidant, and 1.35 parts of antistatic agent.

[0112] Based on Example 1, a control experiment was carried out, specifically Comparative Examples 1 to 4, as described below:

[0113] Comparative Example 1: Comparative Example 1 is based on Example 1, with the following adjustments: no modified polypropylene is added to the raw material, and other processes remain unchanged, specifically:

[0114] In S3, the raw material components include: by weight, 100 parts of homopolymer polypropylene, 13 parts of maleic anhydride grafted polypropylene, 8 parts of modified talc, 8 parts of high-density polyethylene, 0.1 parts of β-nucleating agent, 2.5 parts of styrene-butadiene-styrene block copolymer, 2 parts of lubricant, 0.85 parts of antioxidant, and 1.35 parts of antistatic agent.

[0115] Comparative Example 2: Comparative Example 2 is based on Example 1, with the following adjustments: no maleic anhydride grafted polypropylene is added to the raw material, and other processes remain unchanged, specifically:

[0116] In S3, the raw material components include: by weight, 100 parts of homopolypropylene, 15 parts of modified polypropylene, 8 parts of modified talc, 8 parts of high-density polyethylene, 0.1 parts of β-nucleating agent, 2.5 parts of styrene-butadiene-styrene block copolymer, 2 parts of lubricant, 0.85 parts of antioxidant, and 1.35 parts of antistatic agent.

[0117] Comparative Example 3: Comparative Example 3 is based on Example 1, with the following adjustments: the talc powder in the raw material is not modified, and other processes remain unchanged, specifically:

[0118] In S3, the raw material components include: by weight, 100 parts of homopolymer polypropylene, 15 parts of modified polypropylene, 13 parts of maleic anhydride grafted polypropylene, 8 parts of talc, 8 parts of high-density polyethylene, 0.1 parts of β-nucleating agent, 2.5 parts of styrene-butadiene-styrene block copolymer, 2 parts of lubricant, 0.85 parts of antioxidant, and 1.35 parts of antistatic agent.

[0119] Comparative Example 4: Comparative Example 4 is based on Example 1, with the following adjustments: high-density polyethylene and styrene-butadiene-styrene block copolymer are not added to the raw materials, and other processes remain unchanged, specifically:

[0120] In S3, the raw material components include: by weight, 100 parts of homopolymer polypropylene, 15 parts of modified polypropylene, 13 parts of maleic anhydride grafted polypropylene, 8 parts of modified talc, 0.1 parts of β-nucleating agent, 2 parts of lubricant, 0.85 parts of antioxidant, and 1.35 parts of antistatic agent.

[0121] Performance Test:

[0122] (1) Tensile property test: The high-strength polypropylene material prepared in the embodiment and the comparative example was heated to 210° C. for plasticization, injected into a mold, and pressed to obtain a 1A dumbbell-shaped specimen bar specified in the GB / T 1040.2-2022 standard, and a tensile property test was performed according to the standard;

[0123] (2) Transparency test: The haze of the high-strength polypropylene urine cup prepared in the examples and comparative examples was tested to evaluate the transparency of the high-strength polypropylene urine cup;

[0124] (3) Antistatic test: The surface resistivity of the high-strength polypropylene urine cup prepared in the embodiment and the comparative example was tested to evaluate the antistatic performance of the high-strength polypropylene urine cup.

[0125] The test results of the above tests are shown in Table 1 below:

[0126] Table 1

[0127]

[0128] Result analysis: From the data in Table 1 above, it can be seen that by comparing Example 1 with Examples 2 to 3, it can be seen that the modification degree of the modified polypropylene and the modification degree of the talc in the present invention have a significant effect on the performance of the prepared high-strength polypropylene; by comparing Example 1 with Examples 4 to 5 and the comparative example, it can be seen that by controlling the amounts of modified polypropylene, maleic anhydride grafted polypropylene, modified talc high-density polyethylene, and styrene-butadiene-styrene block copolymer, the present invention synergistically modifies the homopolymer polypropylene to prepare a polypropylene urine cup with high strength, high transparency and certain antistatic properties, which expands the application of polypropylene products in the medical field and is of great significance.

[0129] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A high-strength polypropylene urine cup, characterized in that: The high-strength polypropylene urine cup is made of high-strength polypropylene material; wherein the high-strength polypropylene material includes the following raw materials: by weight, 100 parts of homopolymer polypropylene, 10-20 parts of modified polypropylene, 10-15 parts of maleic anhydride grafted polypropylene, 5-12 parts of modified talc, 5-10 parts of high-density polyethylene, 0.1-0.2 parts of β-nucleating agent, 2-4 parts of toughening agent, 1.5-3 parts of lubricant, 0.5-1 parts of antioxidant, and 1-2 parts of antistatic agent; The preparation method of modified polypropylene comprises the following steps: S11: adding chlorinated polypropylene into toluene, stirring and heating to 50-70° C. to dissolve it, and obtaining a resin solution; S12: heating the resin solution to 90-110° C., adding allyl alcohol polyoxyethylene ether, sodium allyl sulfonate, and an initiator thereto, stirring and reacting for 6-12 hours, and purifying to obtain modified polypropylene.

2. A high-strength polypropylene urine cup according to claim 1, characterized in that: The mass ratio of the chlorinated polypropylene, allyl alcohol polyoxyethylene ether, sodium allyl sulfonate and initiator is 1:(0.2-0.4):(0.05-0.1):(0.02-0.04).

3. A high-strength polypropylene urine cup according to claim 1, characterized in that: The preparation method of the modified talcum powder, The method comprises the following steps: S21: adding talcum powder and dopamine hydrochloride into deionized water, stirring and mixing, adjusting the pH to 7-8, adding horseradish peroxidase into the water, stirring and mixing, then adding hydrogen peroxide into the water, finally heating to 35-50°C, stirring and reacting for 0.5-1.5h, filtering, washing and drying to obtain polydopamine-coated talcum powder; S22: adding polydopamine-coated talcum powder and silane coupling agent into ethanol solution, stirring and heating to 50-60°C for reaction for 1-5h, and Filter, wash and dry to obtain silane-modified talc; S23: add silane-modified talc, 3-[bis-(2-hydroxyethyl)-amino]-benzoic acid and p-toluenesulfonic acid to xylene, stir and heat to 50-60°C for reaction for 4-8h, filter, wash and dry to obtain hyperbranched modified talc; S24: add hyperbranched talc and terminal hydroxyl polybutadiene acrylonitrile to petroleum ether, stir and heat to 30-50°C for reaction for 24-48h, filter, wash and dry to obtain modified talc; The mass ratio of the talc, dopamine hydrochloride and horseradish peroxidase is 10:(0.5-2):(0.001-0.01), wherein the average particle size of the talc is 5-30 nm; the hydrogen peroxide is a 2-4 v / v% hydrogen peroxide aqueous solution, and the ratio of its addition amount to horseradish peroxidase is 1 mL:(0.02-0.1) g; the addition amount of the silane coupling agent is 10-20% of the mass of the polydopamine-coated talc; the mass ratio of the silane-modified talc, 3-[bis-(2-hydroxyethyl)-amino]-benzoic acid and p-toluenesulfonic acid is 1:(0.5-0.8):(0.005-0.008); the mass ratio of the hyperbranched talc and the terminal hydroxyl polybutadiene acrylonitrile is 1:(0.8-1.2).

4. A high-strength polypropylene urine cup according to claim 3, characterized in that: The silane coupling agent includes any one of 3-chloromethyltriethoxysilane, 3-chloropropyltriethoxysilane and 3-chloropropyltrimethoxysilane.

5. The high-strength polypropylene urine cup according to claim 1, characterized in that: The grafting rate of the maleic anhydride grafted polypropylene is 1.2-2%.

6. The high-strength polypropylene urine cup according to claim 1, characterized in that: The β-nucleating agent is a thionamide compound; the toughening agent includes one or a combination of EPDM rubber, EPDM rubber, styrene-butadiene-styrene block copolymer, and butadiene rubber; the lubricant includes one or a combination of zinc stearate, calcium stearate, and magnesium stearate; the antioxidant includes one or a combination of hindered phenol antioxidants, thioester antioxidants, and phosphite antioxidants; and the antistatic agent is N,N-dihydroxyethyl octadecylamine.

7. The high-strength polypropylene urine cup according to claim 1, characterized in that: The preparation method of the high-strength polypropylene material, The method comprises the following steps: S31: placing each raw material component in a mixer according to a formula ratio, stirring and mixing at a rotation speed of 50 to 100 r / min for 10 to 30 minutes to obtain a mixed component; S32: adding the mixed component into a twin-screw extruder, melt blending, extruding and granulating, and obtaining a high-strength polypropylene material.

8. A high-strength polypropylene urine cup according to claim 7, characterized in that: The temperature of the melt blending is 190-230° C., the time of the melt blending is 10-30 min, and the screw speed is 100-200 r / min.

9. A process for preparing a high-strength polypropylene urine cup according to any one of claims 1 to 8, characterized in that: The preparation process is as follows: after the high-strength polypropylene material is plasticized, it is injected into a mold and pressed into shape to obtain a high-strength polypropylene urine cup.

10. The preparation process of a high-strength polypropylene urine cup according to claim 9, characterized in that: The plasticizing temperature is 190-230°C.

Citation Information

Patent Citations

  • Antistatic low haze polypropylene composite material, preparation method and application

    CN102993567A

  • High-yield-strain low-temperature-impact-resistant talcum powder filled polypropylene material and preparation method thereof

    CN112778684A

  • Preparation and construction method of high-hardness polishable art coating

    CN118440552A

  • Automotive dashboard polypropylene composite material and preparation method therefor

    WO2022016787A1

Cited By

  • Composite material for 3D printing and preparation method thereof

    CN120005323A

  • A composite material for 3D printing and its preparation method

    CN120005323B

  • Modified polypropylene plastic cable protection pipe and preparation method thereof

    CN121249052A

  • Modified polypropylene plastic cable protection pipe and preparation method thereof

    CN121249052B